Racism, Discrimination and Inequity During COVID-19 Pandemic - A Review - Maheshwari, Chanchal; Khan, Shehroz; Hussain, Iqra Faraz; Iqbal, Warda (Archives of Clinical and Medical Case Reports, 2024)
The COVID-19 pandemic has dramatically changed the life of a common man throughout the world since its first case was reported in Wuhan, China, during December of 2019. The disease has been a substantial burden on the healthcare, economic, social, educational, and f inancial systems of low-, middle- or high-income countries. It certainly created a lot of stigma among people as on the one side there were doctor’s recommendations and awareness sessions, while on the other hand people started believing in myths and their uncertainty forced them to believe any vague information, even it didn’t take time to generate discrimination, inequity among masses of people throughout the globe. Doctors and front line workers were badly treated, assaulted, spat on, and physically abused as people feared that they were carriers of the disease. There is evidence suggesting that Chinese people were victimized by racism, even Chinese restaurants were shut down as people feared to go in.